Structure-Guided Engineering of a Complement Component C3-Binding Nanobody Improves Specificity and Adds Cofactor Activity - Pedersen, Henrik; Jensen, Rasmus Kjeldsen; Hansen, Annette Gudmann; Petersen, Steen Vang; Thiel, Steffen; Laursen, Nick Stub; Andersen, Gregers Rom (Frontiers in Immunology, 2022)
The complement system is a part of the innate immune system, where it labels intruding pathogens as well as dying host cells for clearance. If complement regulation is compromised, the system may contribute to pathogenesis. The proteolytic fragment C3b of complement component C3, is the pivot point of the complement system and provides a scaffold for the assembly of the alternative pathway C3 convertase that greatly amplifies the initial complement activation. This makes C3b an attractive therapeutic target. We previously described a nanobody, hC3Nb1 binding to C3 and its degradation products. Here we show, that extending the N-terminus of hC3Nb1 renders the resulting EWE nanobody specific for C3 degradation products. By fusing EWE to N-terminal CCP domains from complement Factor H (FH), we generated the fusion proteins EWEnH and EWEµH. In contrast to EWE, these fusion proteins supported Factor I (FI)-mediated cleavage of human and rat C3b. The EWE, EWEµH, and EWEnH proteins bound C3b and iC3b with low nanomolar dissociation constants and exerted strong inhibition of alternative pathway-mediated deposition of complement. Interestingly, EWEnH remained soluble above 20 mg/mL. Combined with the observed reactivity with both human and rat C3b as well as the ability to support FI-mediated cleavage of C3b, this features EWEnH as a promising candidate for in vivo studies in rodent models of complement driven pathogenesis.